Method for synthesis of multi-beam antenna array pattern - S. I. Luzin; I. U. Luzin (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The problem for synthesis of the multi-beam antenna array is considered. We propose amplitude-phase distribution synthesis method based on Fisher information measure. The results of mathematical simulation are discussed.